Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/chem.201702484
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox of Chromones and Quinolones for Measuring a Wide Range of ATP Concentrations

Abstract: A series of 26 3-hydroxychromones, three bis-flavonols and four 3-hydroxyquinolones were studied to evaluate their fluorescence response to interaction with ATP in buffer. The dyes differ by the total charge, the size and number of their aromatic units, as well as the position or electron-donating ability of their substituents. All of them were suggested to form complexes with ATP of 1:1 and 1:2 stoichiometry, which can be evidenced by their bright fluorescence and their 3000-6000 cm red-shifted excitation ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
15
0
2
Order By: Relevance
“…[18] Pivovarenko and co-workersd iscovered that 3-hydroxyflavones could bind and detect ATPi na queous solution in ab road concentrationr ange. [19] Among al argen umber of the investigated chromones and quinolones,t he authors found that hydroxyland dialkylamino-derivatives (18,19)d isplay an ew bathochromically shifted band in the presence of ATPi na queous solution. Ther ecognition process is accompanied by as trong fluorescencei ncrease (30-50-fold).I ti sp roposed that adenine interacts with the dye, releasing the water from the dye, whereas the OH groups can form hydrogen bonds with basic atoms of the nucleotide.…”
Section: Functional Dyes For Nucleotide Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Pivovarenko and co-workersd iscovered that 3-hydroxyflavones could bind and detect ATPi na queous solution in ab road concentrationr ange. [19] Among al argen umber of the investigated chromones and quinolones,t he authors found that hydroxyland dialkylamino-derivatives (18,19)d isplay an ew bathochromically shifted band in the presence of ATPi na queous solution. Ther ecognition process is accompanied by as trong fluorescencei ncrease (30-50-fold).I ti sp roposed that adenine interacts with the dye, releasing the water from the dye, whereas the OH groups can form hydrogen bonds with basic atoms of the nucleotide.…”
Section: Functional Dyes For Nucleotide Sensingmentioning
confidence: 99%
“…Interestingly, amphiphilic dye 17 can also form self‐assembled structures but with a micelle‐like structure, which can bind ATP on its outer surface resulting in fluorescence enhancement . Pivovarenko and co‐workers discovered that 3‐hydroxyflavones could bind and detect ATP in aqueous solution in a broad concentration range . Among a large number of the investigated chromones and quinolones, the authors found that hydroxyl‐ and dialkylamino‐derivatives ( 18 , 19 ) display a new bathochromically shifted band in the presence of ATP in aqueous solution.…”
Section: Functional Dyes For Nucleotide Sensingmentioning
confidence: 99%
“…The interaction of DMHF with nucleotides and a computer aided simulation on the geometry of DMHF∙ATP complexes in vacuo was also reported. A recent study by the same authors describe further flavones with various association constants [ 45 ], however, none of them are the result of rational design.…”
Section: Introductionmentioning
confidence: 99%
“…Ратіометричні зонди містять у своєму складі кілька додаткових елементів, таких як донор та акцептор енергії (у FRET-зондах [22,24]) або два однакові флуорофори, як у ексимерних зондах [22]. Важливим кроком на шляху до спрощення структури АТФ-зондів є розробка конструкцій на основі флавонолу та його ізостер: 3-гідрокси-4'-(диметиламіно)флавон (FME) [28,29] і похідні хромону та хінолону [30]. Зонд FME, синтетичний аналог природних флавонолів [31,32], незважаючи на просту будову, дає високоселективну флуоресцентну відповідь при зв'язуванні з АТФ порівняно з іншими нуклеотидами у водних буферних розчинах [29].…”
unclassified
“…З допомогою цього зонду була здійснена реєстрація виділення АТФ мітохондріями під впливом сукцинату in vitro [28]. Остання публікація [30] свідчить, що 31 з 33 досліджених флавонів та хінолонів різної будови та заряду дають потужну флуоресцентну відповідь при зв'язуванні з АТФ і можуть бути ефективно застосовані у водних розчинах для виявлення АТФ у концентраційних межах 1-50000 мкМ.…”
unclassified